PENGARUH TRUST CORPORATE DAN MARKETING COMMUNICATION TERHADAP CUSTOMER SATISFACTION PADA PERUSAHAAN JASA PT AAJI MANULIFE SURABAYA - Nur jannah (Universitas 17 Agustus 1945 Surabaya, 2019)
This study aims to determine the effect of corpoarate trust and marketing communication oncustomer satisfaction on PT. AAJI Insurance Manulife Surabaya. This type of research issurvey research that uses or has used insurance services at PT.AAJI Manulife Surabaya. Thesampling technique accidental sampling, so that the number of samples obtained is 100people. The technique of collecting data uses questionnaires and tabulations that have beentested for validity and reliability. The data analysis technique used is multiple linearregression. The results of this study found that there is a simultaneous influence of corporateand communication trust on customer satisfaction and empirically the partial effect thatcorporate trust has a positive and significant effect on customer satisfaction and marketingcommunication has a positive and significant effect on customer satisfaction.Keywords: Corporate trust, Marketing Communication, Customer Satisfaction